Mentransformasikan Efisiensi Anggaran dan Kompetensi Menjadi Kinerja melalui Perilaku Kerja Inovatif - Rio Eka Putra; Eka Mariyanti (CV. ITTC INDONESIA, 2026)
Budget efficiency in public sector organizations does not always lead to improved performance when cost saving policies focus solely on reducing expenditure without corresponding improvements in work practices. This study examines the effects of budget efficiency and employee competence on employee performance at the West Sumatra Provincial DPRD Secretariat, with innovative work behavior as a mediating variable. This study employed a quantitative approach and used total sampling involving 99 employees. Data collected through questionnaires were analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4. The findings indicate that budget efficiency does not directly improve employee performance but significantly promotes innovative work behavior. Employee competence is shown to improve performance while also encouraging innovative work behavior. These findings suggest that the benefits of budget efficiency can only be realized when resource constraints encourage employees to streamline processes, improve procedures, utilize technology, and develop more effective working methods. Conversely, innovative work behavior does not mediate the effect of employee competence on performance because competence is primarily applied directly in task completion. These results provide an empirical explanation of the mechanism through which budget efficiency is translated into public-sector performance outcomes. This study emphasizes that budget-efficiency policies should be accompanied by organizational support for the implementation of new ideas, opportunities for employees to improve work processes, and competency development aligned with job requirements. The alignment of budgetary policies, competency enhancement, and the institutionalization of innovation provides an essential foundation for sustainably improving public-sector organizational performance and the quality of administrative support for the Regional House of Representatives in carrying out its functions.